Foreign Investment of Hi-Tech Enterprises as the Source of Knowledge Transfer to the Region — Opolskie Voivodship Case Study - Anna Jasińska-Biliczak; Hana Stverkova; Ilona Winiarczyk (Barometr Regionalny, 2018)
Article’s aim is the critical analysis of the literature and case study of the knowledge transfer issue into Opolskie Voivodship by foreign investment of the hi-tech sector. To illustrate such undertaken problem the role and a place of knowledge transfer and high technologies sector as the factor having an impact on development of the region was discussed. Enterprises — foreign investors — are the source of the knowledge for human capital of the region, and because of that for enterprises of the region. There also will be pointed the practical example from Opolskie Voivodship, at the base of knowledge transfer by hi-tech enterprise into Opolskie Voivodship. After such stated analysis it is possible to state that foreign investment of hi-tech sector and knowledge transfer to region being their consequence, constitute actual field of scientific interests. As the pro-innovative action it is simultaneously the field of the mutual cooperation of hi-tech sector and regional economy. Interactions of these subjects are important not only from the point of view of mutual benefits, such as knowledge transfer by the side of regional economy and economic benefits, including those connected to regional human capital, by the side of hi-tech sector. Thus foreign investment of that sector can be pointed as the source of innovation, know-how and knowledge transfer, but also as the engines of social and economic changes in the region.